The Concept and Context of Distance Learning in the New Normal Learning Scheme - Januard Deñola Dagdag; Ronnie Jay S. Darang (Pedagogi: Jurnal Ilmu Pendidikan, 2021)
Distance Learning has been around since its advent in 1960 and evolved in the creation of World Wide Web (WWW) in 1991 with the introduction of first education programs through internet of University of Phoenix and other universities and colleges. Vast ideas of concepts, theories and context have aroused in the popularization and implementation of distance learning in educational system and its first and most adversary are those in favor of lecture style of teaching. In the onset of the COVID-19, all fields of society have been affected and one of it is the educational system. This pandemic propagated the rise of distance learning in the Philippines and it becomes the most reliable modality of continuing the academic years. Distance learning becomes more adaptive and effective with the help of flexible teaching and learning modalities. Several studies exposed the concepts and theories for the distance learning to be more acceptable. These concepts and theories are supported by the literature with claims of context of distance learning in order to create an open and good system. Frameworks and being literate with the aid of continuous studies in this rising field is one of the key concepts in creating more possibilities to attain the quality of sufficient distance learning modality.